2022
DOI: 10.21037/atm-22-2330
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of analytical methods for 15 hazardous drugs by UPLC-Q/Orbitrap-HRMS

Abstract: Background: Cytotoxic drug residues in pharmacy intravenous admixture services (PIVAS) have always been a major problem for pharmaceutical workers and the PIVAS environment,which is not only pollutes the PIVAS environment, but also causes serious harm to the life and health of the staff. This study aimed to establish an ultra-high performance liquid chromatography quadrupole orbitrap high resolution mass spectrometry (UPLC-Q/Orbitrap-HRMS) method for the rapid detection and monitor of 15 cytotoxic drugs.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Occupational exposure to drugs and its association with adverse health effects has been well demonstrated over the decades, especially antineoplastic drugs (Yu et al, 2022). Previous studies have demonstrated that the environmental pollution caused by leakage causes physiological damage to PIVAS staff, and long-term occupational exposure also causes injuries to staff, especially for cytotoxic drugs (Connor et al, 2014;Hao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational exposure to drugs and its association with adverse health effects has been well demonstrated over the decades, especially antineoplastic drugs (Yu et al, 2022). Previous studies have demonstrated that the environmental pollution caused by leakage causes physiological damage to PIVAS staff, and long-term occupational exposure also causes injuries to staff, especially for cytotoxic drugs (Connor et al, 2014;Hao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Raveena confirmed that environmental contamination plays a role in biological exposure to cyclophosphamide (Raveena et al, 2015). Some studies focused on antineoplastic drug residue monitoring, for example, ultra-high pressure liquid chromatography separation coupled to tandem mass spectrometry detection (UHPLC-MS/MS) methods for the detection of surface samples (Fleury et al, 2022), ultra-high performance liquid chromatography quadrupole orbitrap high resolution mass spectrometry (UPLC-Q/Orbitrap-HRMS) method for the rapid detection and monitor of 15 cytotoxic drugs in PIVAS (Yu et al, 2022). Other studies focused on the health risks associated with occupational exposures to antineoplastic drugs, and the findings were generally indicative of an increased risk of adverse reproductive outcomes with occupational exposure (Connor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prolonged placement of finished infusion solutions can decrease drug concentrations, preventing the timely achievement of effective therapeutic concentrations and increasing the risk of bacterial resistance. [16][17][18] Therefore, leaving a finished infusion with unstable properties for too long may cause drug degradation and affect the drug's therapeutic effect. The number of particles in the infusion may also increase and the physical and chemical properties of the infusion may change, resulting in outcomes such as discoloration and precipitation.…”
Section: Introductionmentioning
confidence: 99%